Mass closure versus layered closure of midline laparotomy incisions: a prospective comparative study - Deshmukh, Santoshkumar N.; Maske, Audumbar N. (International Surgery Journal, 2018)
Background: The ideal method of abdominal wound closure remains to be discovered. It should be technically so simple that the results are as good in the hands of a trainee as in those of the master surgeon. The best abdominal closure technique should be fast, easy, and cost effective while preventing both early and late complications. Present study is undertaken to compare the two methods (Mass closure and Layered closure) of laparotomy wound closure in relation to post-operative complications, time for wound closure and cost effectiveness in both groups and also to decide the most effective method among the two. Methods: This prospective comparative study was conducted in department of surgery at a tertiary care teaching hospital at Solapur (Maharashtra) from January 2006 to January 2009. On admission, patients suspected of having intraabdominal pathology, a thorough clinical e and general assessment was done. Necessary radiological and biochemical investigations were done to support the diagnosis. After confirmation of diagnosis patients were subjected for exploratory laparotomy. The laparotomy wound was closed with either by Mass closure or Layered closure technique. Patients were followed up for 6 months in post-operative period for detection late complications. Results: Total 60 patients of were studied. Majority of patients were in 61 to 65 age group. Male outnumbered the females. Incidence of early complications like seroma, wound infection is more in layered closure group as compared to mass closure. Mean wound closure time is more in layered closure group. Mass closure technique is more cost effective than layered closure group. Conclusions: Mass closure technique is less time consuming, more cost effective and safe for closure of midline laparotomy incisions.